South Sudan Economic Brief : April 2019 - World Bank (Washington, DC, 2022)
The economy is estimated to have contracted by 3.5 percent during FY2017-2018, but a modest recovery is projected for FY2018-2019. Coupled with economic mismanagement, many years of conflict have eroded the productive capacity of South Sudan. Conflict persists across the country despite the peace agreement and is the major driver of the economic collapse. Oil production is expected to be the major driver of growth in the short and medium term. South Sudan remains in debt distress and the external position is weak, with depleted reserves estimated at less than one week of import cover. If the peace agreement is respected by all parties and conflict does not recur, the economy is projected to grow by 1.8 percent during FY2018-2019. However, a less positive outlook could emerge if the peace agreement falters, with growth barely reaching 0.3 percent in the absence of progress in the non-oil sectors.